Analysis bibliometrics study reasoning mathematical in mathematics education: trends, structures, and implications for elementary school education - Yunni Arnidha; Agus Suyatna; Sugeng Sutiarso (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Mathematical reasoning is a fundamental competency in mathematics education that supports students' logical, critical, and systematic thinking skills. Along with technological advancements and the growing demands of twenty-first-century learning, research on mathematical reasoning has expanded significantly and become increasingly multidisciplinary. This study employed a bibliometric analysis to map the global development of research on mathematical reasoning in mathematics education. Data were retrieved from the Scopus database using the keywords "mathematical reasoning" and "learning". A total of 685 documents published between 1979 and 2026 were analyzed using Biblioshiny. The analysis focused on identifying publication trends, thematic structures, collaboration patterns, and the geographical distribution of research contributions. The results reveal a substantial increase in publications, particularly since 2006, with research productivity peaking in 2023. The field is organized around three major domains: pedagogical aspects of mathematics learning, mathematical modeling development, and technology integration, including artificial intelligence and machine learning. Furthermore, research contributions are predominantly led by the United States and China, supported by strong international collaboration networks. This study concludes that mathematical reasoning research has evolved into a global, interdisciplinary, and technology-oriented field. However, its implementation in elementary mathematics education remains relatively limited. The findings provide a comprehensive overview of the development of research on mathematical reasoning and offer insights for designing more contextually grounded and practice-oriented mathematics learning approaches at the elementary school level.